ANALISIS MODEL MENGENAI NILAI, REWARD, MOTIVASI, KOMITMEN ORGANISASIONAL DAN KINERJA PADA PEGAWAI DINAS KOMUNIKASI INFORMATIKA DAN STATISTIK KABUPATEN BREBES - Agung Budiman; Grace Tianna Solovida (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this study was to test and analyze the effect of value, reward, motivation, organizational commitment and performance on employees of the information and statistics communication agency of brebes regency. The population in this study are all employees of the information communication office and kab statistics. Brebes totaling 113 people. The sampling technique used is the census method. Data collection is done through a questionnaire. Testing the hypothesis in this study was carried out by analysis of structural equation modeling or sem. Based on the results of the study it is known that value has a positive effect on work motivation. Reward have a positive and significant effect on work motivation. Motivation has a positive effect on organizational commitment. Organizational commitment has a positive and significant effect on employee performance